Measuring the Contribution of Volunteering to the Sustainable Development Goals: Challenges and Opportunities - Haddock, M.; Devereux, Peter (2016)
As with the Millennium Development Goals, the UN’s Post-2015 Sustainable Development Goals (SDGs) will only be achieved with the active engagement of volunteers. Volunteer contributions to sustainable development are distinctive. Volunteers’ close engagement with communities in need, their skills and motivation to contribute to more inclusive, active and cohesive societies, and modeling/facilitation of the reciprocal exchange of knowledge and skills among stakeholders make volunteers distinctive actors in support of the achievement of the SDGs. This paper discusses options for documenting and showcasing the collective contributions of a diverse community of volunteers to sustainable development, in the context of recently adopted Sustainable Development Goals (SDGs).